Urgensi Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2020 Tentang Perubahan Ketiga Atas Undang-Undang Nomor 1 Tahun 2015 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 Tentang Pemilihan Gubernur, Bupati, dan Walikota Menjadi Undang-Undang - Sariati, Eka; Nirahua, Salmon Eliazer Marthen; Sedubun, Victor Juzuf (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Government Regulation in Lieu of Law Number 2 of 2020 has provided a legal basis for the implementation of the Pilkada in 2020, the voting was conducted in December 2020.Purposes of the Research: This writing aims to find out and understand about the right legal products in the implementation of regional elections during the Pandemic.Methods of the Research: The research method used is normative juridical. which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The issuance of Government Regulations in Lieu of Law Number 2 Year 2020 is not yet correct, There have been too many changes that have emerged for Law No. 1 of 2015. Then Based on Appendix II number 237 of Law no. 12 of 2011, the Government should understand that if a change in laws and regulations results in a change in systematics, the changed material is more than 50%, or its essence changes, it is better if it is revoked and rearranged in a new form. Parameters of Matters that forced the issuance of Perppu Number 2 of 2020, namely First, the Non-natural disaster Pandemic Corona Virus Disease 2019 (Covid-19) which has caused many casualties; Second, namely the absence of law or there is a law but it is not sufficient